Effect of hydrogen cyanamide on the endogenous hormonal content of pea seedlings (Pisum sativum L.) - Guevara Berger, Eric (2008)
Hydrogen cyanamide (HC) has been used to break bud and seed dormancy and to improve rooting in several species, responses usually associated with the action of plant hormones. However, very few studies have measured endogenous hormones after HC treatment. Therefore, pea (Pisum sativum L.) seedlings with two fully developed internodes above the first leaf were sprayed with 0, 0.1 and 0.3% (v/v) HC. Endogenous concentration of indole-3-acetic acid (IAA), abscisic acid (ABA), zeatin/zeatin riboside and N6(Δ2-isopentenyl) adenine/ N6(Δ2-isopentenyl) adenosine were measured by radioimmunoassay 31 and 80 h after HC treatment. A significant increase in ABA and cytokinin (CK) levels was observed 31 h after treating the plants with 0.3% HC. Small necrotic spots were also noticed in this treatment, thus revealing a toxic effect of this treatment. Additionally, at 80 h, a significant increase in IAA was found for both HC concentrations applied. The action of HC upon ABA, CKs and IAA endogenous levels is discussed.